Periosteal preservation: a new technique in resection of bone high-grade malignant tumors in children—about eleven cases - Mahmoud Smida; Ameni Ammar; Faten Fedhila; Wiem Douira; Samia Sassi (World Journal of Surgical Oncology, 2022)
Abstract Objective The purpose of this study was to describe a surgical technique of bone resection with periosteal preservation and reconstruction in patients with high-grade bone malignant tumors and to determine its effect on local recurrences, and time and quality of bone union in bone autografting reconstruction. Patients and methods We retrospectively reviewed 11 cases of high-grade malignant bone tumors in children aged 4 to 16 years, who were treated with chemotherapy and tumor resection while preserving partially the adjacent periosteum. Tumors were located in the lower limb in eight cases; three tumors were in the humerus. The mean length of the bone defect after resection was 15.8 cm (range, 6–34.5 cm). Reconstruction was provided by non-vascularized autograft in eight cases (lower limb) and polymethyl methacrylate spacer in three cases (upper limb). Patients were followed up for a mean of 71 months. Results At the last follow-up, no patients had local recurrence. Three patients were dead because of metastasis. Bone union was good in time and quality in all children who had bone autografting. In cases of PMMA reconstruction, there was periosteal bone formation around the spacer. According to the MSTS functional score, patients with lower limb localizations had a mean score of 27.75 points and patients with upper limb localizations had a score of 24/30. Conclusion Preservation of the periosteum in bone resection for malignant tumors could be a good adjuvant alternative for bone reconstruction, without increasing the risk of local recurrence. However, patients must be carefully selected.